Impact of proton-induced transmutation doping in semiconductors for space applications12. Issue 29 (5th July 2019) - Logan, Julie V.; Short, Michael P.; Webster, Preston T.; Morath, Christian P.; Steenbergen, Elizabeth H.
Abstract : Proton irradiation typical of detector lifetime in orbit does not change semiconductor chemistry sufficiently through transmutation to alter device performance. Abstract : Critical satellite-based electronics can fail due to irradiation with Van Allen belt trapped protons. While nuclear-reaction-induced transmutation damage is typically ignored, a recent study raised the question of its potential importance in explaining anomalous trends in III–V nBn device operation. To investigate this postulation and to generally quantify the importance of transmutation in semiconductors for space applications, transmutation rates occurring in eight prominent semiconductor systems irradiated with typical device qualification protons of 63 MeV and operating in LEO, MEO, and GEO orbits are examined computationally employing FISPACT-II (validated through experiment and GEANT4 simulations). It is found that the transmutation realized in the III–V nBn device is three orders of magnitude less than would have been required to bring experiment into agreement with theory and that, furthermore, the total transmuted elemental concentrations never exceed 10 10 cm −3 in any semiconductor at the end of 10 years of operation in any orbit considered. Thus, the effect of nuclear transmutation can be safely neglected in predicting modern device operation in orbit.